2006
DOI: 10.1177/0272431606288551
|View full text |Cite
|
Sign up to set email alerts
|

Who Is Offering and How Often? Gender Differences in Drug Offers Among American Indian Adolescents of the Southwest

Abstract: This exploratory study examines gender differences in the patterns of drug offers among a sample of 71 American Indian middle school students. Participants respond to an inventory of drug-related problem situations specific to the cultural contexts of Southwestern American Indian youth. They are asked to consider the frequency of drug offers from specific groups in their social networks and the difficulty associated with refusing drugs from various offerers. The results indicate that female and male American I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…According to this theory, girls in the study may have considered resistance strategies that would mitigate discord among significant family members in their lives, in order to prevent relational disconnections among those family members. The present findings are also are consistent with gender-specific research on other indigenous populations, which has described the unique and intense relational challenges that indigenous girls face when offered drugs from immediate and extended family members (Dixon-Rayle et al, 2006; Okamoto et al, 2010). Specifically, these studies found that indigenous girls experienced drug-related problem situations with family members more frequently than indigenous boys, and that they had more difficulty in dealing with these situations than their male counterparts.…”
Section: Discussionsupporting
confidence: 89%
“…According to this theory, girls in the study may have considered resistance strategies that would mitigate discord among significant family members in their lives, in order to prevent relational disconnections among those family members. The present findings are also are consistent with gender-specific research on other indigenous populations, which has described the unique and intense relational challenges that indigenous girls face when offered drugs from immediate and extended family members (Dixon-Rayle et al, 2006; Okamoto et al, 2010). Specifically, these studies found that indigenous girls experienced drug-related problem situations with family members more frequently than indigenous boys, and that they had more difficulty in dealing with these situations than their male counterparts.…”
Section: Discussionsupporting
confidence: 89%
“…The curriculum incorporated core components of efficacious substance use prevention programs but included modifications that addressed cultural and social influences on the substance use vulnerability and resilience of these youth found in prior research, including key family influences on substance use (Kulis & Brown, 2011; Kulis et al, 2006; Kulis, Reeves et al, 2011; Okamoto et al, 2004; Rayle et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…In addition to avoiding drug offer situations, they employ passive strategies to evade using substances while remaining present when offers occur, redirecting attention from the substance offer by changing the subject or using humor (Kulis & Brown, 2011; Kulis, Reeves, Dustman, & O’Neill, 2011). Such non-confrontational approaches allow UAI youth to remain in social situations and preserve relationships in family networks where many substance offers occur (Kulis, Okamoto, Rayle, & Sen, 2006; Okamoto, LeCroy, Dustman, Hohmann-Marriott, & Kulis, 2004; Rayle et al, 2006; Waller, Okamoto, Miles, & Hurdle,2003). …”
Section: Introductionmentioning
confidence: 99%
“…Based on her research on adolescent cigarette use, Unger (2003) concluded that peer influence on smoking was strongest among Indigenous youth than for the other racial/ethnic groups in the study sample. Peer influences have been shown to vary by gender among Indigenous youth in the southwest, where Rayle and colleagues (2006) found that girls reported significantly more drug offers and had more difficulty refusing drugs than did boys; the majority of these drug offers came from cousins, friends, and older peers. Taken together, this body of research suggests that Indigenous youth peer networks often include relatives, and that these networks may be more influential to the onset of substance use than has been found for youths of other race/ethnicities, particularly so for Indigenous girls.…”
Section: Literature Reviewmentioning
confidence: 99%